DARI PENYANGKALAN MENUJU SADRAH: REPRESENTASI KEPASRAHAN DALAM LIRIK LAGU FOR REVENGE - Arik Fajar Cahyono; Gayatri Mayang Handayani (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to analyze the lyrics of For Revenge as a representation of a servant’s spiritual journey in confronting affliction, employing Charles Sanders Peirce’s semiotic framework. The analysis focuses on four songs from the album Sebelum Merayakan: Penyangkalan, Semula, Sadrah, and Menunggu Giliran. Using a qualitative-interpretive method, the study maps Peirce’s three principal semiotic elements: representamen (sign), object (emotional experience), and interpretant (spiritual meaning within an Islamic perspective). The findings reveal a narrative structure that progresses through several spiritual phases: denial of destiny, self-introspection (muhasabah), surrender to God (tawakal), and awareness of mortality (dzikrul maut). Although the lyrics are explicitly secular in form, they can be reinterpreted as a spiritual medium, since meaning is never singular and is shaped by the interpretive horizon of the audience. This study demonstrates that popular music, particularly the emo genre, can serve as a vehicle for religious contemplation for listeners with particular faith-based backgrounds. These findings affirm that products of popular culture are not detached from the spiritual sphere; rather, they may function as a bridge between artistic expression and religious values.